A review of the nutritional value of legumes and their effects on obesity and its related co‐morbidities. Issue 5 (17th January 2014) - Rebello, C. J.; Greenway, F. L.; Finley, J. W.
Summary Since the 1970s, the proportion of overweight and obese people in the United States has grown at an alarming rate. An awareness of the consequences of obesity on the health and well‐being of individuals is evident in the plethora of strategic plans at the local and national levels, most of which have largely fallen short of their goals. If interventions continue to be unsuccessful, it is estimated that approximately three of four Americans will be overweight or obese by 2020. Prevention of excess weight gain can be accomplished with relatively small changes in lifestyle behaviours to control body weight. Small sustainable changes are perhaps better than efforts to achieve larger changes that cannot be sustained. Legumes can be a valuable food by which the needs of the undernourished or under‐served populations could be met. They can be incorporated into meat products, such as sausages and burgers, to lower the energy density of these foods while providing important nutrients. Replacing energy‐dense foods with legumes has been shown to have beneficial effects on the prevention and management of obesity and related disorders, such as cardiovascular disease, diabetes and the metabolic syndrome. This review explores the nutritional value and obesity‐related health benefits of legume consumption while focusing on pulses.